Розвиток та ефективне використання людського капіталу в ринкових умовах господарської діяльності будівельних організацій - Малихіна, О. М. (Ways to Improve Construction Efficiency, 2012)
The essence of each of the most known estimation models is investigated and the expedient area of their practical application in the conditions of the Ukrainian enterprises activity is defined fulfilled.